Why do males emerge before females? Sexual size dimorphism drives sexual bimaturism in insects. (15th June 2021) - Teder, Tiit; Kaasik, Ants; Taits, Kristiina; Tammaru, Toomas
ABSTRACT: Conspecific females and males often follow different development trajectories which leads to sex differences in age at maturity (sexual bimaturism, SBM). Whether SBM is typically selected for per se (direct selection hypothesis) or merely represents a side‐effect of other sex‐related adaptations (indirect selection hypothesis) is, however, still an open question. Substantial interspecific variation in the direction and degree of SBM, both in invertebrates and vertebrates, calls for multi‐species studies to understand the relative importance of its evolutionary drivers. Here we use two complementary approaches to evaluate the evolutionary basis of SBM in insects. For this purpose, we assembled an extensive literature‐derived data set of sex‐specific development times and body sizes for a taxonomically and ecologically wide range of species. We use these data in a meta‐analytic framework to evaluate support for the direct and indirect selection hypotheses. Our results confirm that protandry – males emerging as adults before females – is the prevailing form of SBM in insects. Nevertheless, protandry is not as ubiquitous as often presumed: females emerged before males (= protogyny) in about 36% of the 192 species for which we had data. Moreover, in a considerable proportion of species, the sex difference in the timing of adult emergence was negligible. In search for the evolutionary basis of SBM, we found stronger support for the hypothesis that explains SBM by indirect selection. First, across species, the direction and degree of SBM appeared to be positively associated with the direction and degree of sexual size dimorphism (SSD). This is consistent with the view that SBM is a correlative by‐product of evolution towards sexually dimorphic body sizes. Second, within protandrous species, the degree of protandry typically increased with plastic increase in development time, with females prolonging their development more than males in unfavourable conditions. This pattern is in conflict with the direct selection hypothesis, which predicts the degree of protandry to be insensitive to the quality of the juvenile environment. These converging lines of evidence support the idea that, in insects, SBM is generally a by‐product of SSD rather than a result of selection on the two sexes to mature at different times. It appears plausible that selective pressures on maturation time per se generally cannot compete with viability‐ and fecundity‐mediated selection on insect body sizes. Nevertheless, exceptions certainly exist: there are undeniable cases of SBM where this trait has evolved in response to direct selection. In such cases, either the advantage of sex difference in maturation time must have been particularly large, or fitness effects of body size have been unusually weak.